Cryptographic System for Mobile Application (Automated Resume Builder) - Idoko, Bartholomew; Agada, Sampson; Isah, Okoro Denis; Bossah, Chika Patricia (Darul Yasin Al Sys, 2025)
This paper presents a secure and user-friendly approach for developing an automated mobile application system, using a resume builder as a case study. The proposed system automates the construction of resumes by utilizing applicants’ information as input, allowing users to create, edit, delete, read, and save resumes in PDF format, supported by login and signup via OTP verification. To enhance security, the study introduces a two-factor authentication (TFA) scheme that integrates a cryptographic-compatible device and a password, offering stronger protection against risks such as communication breaches, device or server vulnerabilities, and offline or online credential attacks. The TFA is implemented through shared access signature (SAS) message authentication or other PIN-based authentication methods. The system architecture incorporates an enhanced cryptographic framework adaptable to various password-based client–server authentication protocols, reducing reliance on less secure single-layer password systems. Data encryption is handled using the Advanced Encryption Standard (AES), chosen over 3DES for its superior processing efficiency, while the Message-Digest Method (MD5) algorithm is used to hash user-defined encryption keywords. All server-side data, including encryption keys, remain encrypted, ensuring that unauthorized access yields no advantage. By enabling users to encrypt and decrypt data with AES and securing encryption keys via MD5 hashing, the system improves both privacy and security in mobile applications. The study contributes to secure software design by demonstrating how cryptographic methods can be modularly integrated into mobile systems, addressing the cybersecurity gaps of conventional job search and resume platforms.